Critical success factors of construction projects in Jordan : An empirical investigation - A. M., Faten Albtoush; S. I., Doh; R. A., Rahman; A. H., Al-Momani (Springer Science and Business Media Deutschland GmbH, 2022)
The construction sector is considered one of the most important engines of the national economy in any country; in addition to that, it clearly contributes to improving the quality of life of individuals. In the construction industry, project success is crucial, because it reflects positively on the growth of the national economy, in partnership with other sectors related to it directly and indirectly. However, construction projects often come with disappointment in completion within time, cost, and quality, for multiple reasons throughout the project life cycle. The aim of this study is to determine the factors that affect the success of construction projects, based on realistic project data. To achieve this goal, data were collected and analyzed from the final reports of a number of projects that had been implemented in 15 years. The result illustrates that the most significant and vital factors for the success of the construction project are: quality-related factors, cost-related factors, time-related factors, contract-related factors, and related external factors. Results help project stakeholders improve construction project performance by identifying factors that have affected project success. This allows them to take appropriate measures for every worker to ensure the success of their projects. In addition, this study contributes to the current body of knowledge by being one of the few studies that analyze project data to identify critical success factors for construction projects in developing countries.